Effect of Barbed Hooks Used in the Longline Fishing Operations Operated along the Panambur Coast off Mangaluru - Nikhil, A. N.; Naik, Jaya; Varadaraju, S.; Badami, S. H.; Annappaswamy, T. S.; Atnur, V. S. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during August, 2024–September, 2025 at Panambur coast off Mangaluru, Karnataka, India to investigate the operational efficiency, hooking ability and economic viability of barbed hooks used in longline fishing operations along the Panambur coast off Mangaluru, Karnataka. The primary objective was to evaluate the performance of barbed hooks in terms of catch composition, species selectivity, fuel consumption, and profitability under real world fishing conditions. Field trials were conducted over a 255-day period using a fiber-reinforced plastic longliner powered by a 9.9 hp outboard engine. The fishing gear comprised a two hundred meter nylon monofilament mainline with one hundred branch lines, each fitted with stainless steel barbed hooks and baited with live fish. Fishing operations were carried out at a depth of approximately 30 m, with catch data, fuel usage and operational parameters meticulously recorded. The results demonstrated that barbed hooks achieved an average hooking efficiency of 0.52, with peak performance observed on the 19th day. The catch composition was dominated by Skipjack Tuna, followed by King Mackerel and Barracuda, indicating high selectivity for commercially valuable species. Fuel consumption averaged seventy l trip-1, reflecting cost-effective operations. The study highlighted the effectiveness of barbed hooks in enhancing catch rates while maintaining economic and ecological sustainability. These findings supported the continued use of barbed hooks in small-scale longline fisheries and provided a scientific basis for gear standardization and policy recommendations aimed at improving resource utilization and fisher livelihoods along the Indian coast.